40 Ar/39Ar hornblende ages from southwestern Maine: evidence for Late Paleozoic metamorphism - West, David; Lux, Daniel; Hessey, Arthur (Atlantic Geology, 1988)
⁴⁰/Ar/⁳⁹ Ar analyses of hornblendes from a 120 km long NE-trending transect within die high-grade rocks of the Casco Bay Group provide information regarding the timing of thermal events and subsequent cooling history of this region. In die north, plateau ages of 368-372 Ma record the time of cooling dirough argon closure temperatures (500°C) following Acadian metamorphism. In die central portion of the transect, hornblendes display younger ages (350-323 Ma) and release spectra which show evidence of a Late Paleozoic thermal overprint. To the soudi, significantly lower plateau ages are recorded (270-290 Ma). These lower ages date either die time of a Late Paleozoic diermal event or the time of cooling following a prolonged period of burial at deep crustal levels. The former interpretation is favored on the basis of the disturbed release spectra in the central portion of the transect and the fact that ages over the 60 km long southern portion of die transect are relatively constant at 280±10 Ma. If a Late Paleozoic thermal event occurred in this region it was evidently not accompanied by large amounts of deformation as structural evidence for such an event is lacking. The exact nature of the Late Paleozoic resetting of hornblendes in this portion of the Casco Bay Group is not clear; however, it may be related to die events which lead to granite emplacement 275 Ma ago in die Massabesic Gneiss Complex and the 272-282 Ma ages for monazites from die nearby Sebago Batholith.